2017
DOI: 10.5713/ajas.16.0839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfalfa flavonoids extract on the microbial flora of dairy cow rumen

Abstract: ObjectiveThe effect of flavonoids from alfalfa on the microbial flora was determined using molecular techniques of 16S ribosome deoxyribonucleic acid (rDNA) analysis.MethodsFour primiparous Holstein heifers fitted with ruminal cannulas were used in a 4×4 Latin square design and fed a total mixed ration to which alfalfa flavonoids extract (AFE) was added at the rates of 0 (A, control), 20 (B), 60 (C), or 100 (D) mg per kg of heifer BW.ResultsThe number of operational taxonomic units in heifers given higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…As it was the case in this study, Bacteroidetes and Firmicutes are the major bacterial phyla in both dairy cattle and buffaloes (50,(87)(88)(89)(90). A linear increase in Firmicutes was observed together with a decrease in Bacteroidetes.…”
Section: Rumen Bacterial Diversitysupporting
confidence: 73%
“…As it was the case in this study, Bacteroidetes and Firmicutes are the major bacterial phyla in both dairy cattle and buffaloes (50,(87)(88)(89)(90). A linear increase in Firmicutes was observed together with a decrease in Bacteroidetes.…”
Section: Rumen Bacterial Diversitysupporting
confidence: 73%
“…Parabacteriodes is a typical component of mammalian GI microbiotas, including those of humans and chimpanzees 23 . Asteroleplasma is a poorly characterized genus within the Tenericutes, but two recent studies have identified these bacteria as part of the rumen microbiota 24 , 25 , suggesting that they may play a role in cellulose degradation. The taxonomic assignment of these OTUs should be interpreted with caution as both were classified with low confidence.…”
Section: Discussionmentioning
confidence: 99%
“…A major goal of livestock production system today is restriction of using antibiotics and other synthetic medicinal chemistry as feed additives and growth promoters, versus natural growth promoters (NGPs) as effective alternatives to those products. Using antibiotic in ruminant nutrition as a supplement are widely applied to alter rumen fermentation and methane emission but due to the extreme of using antibiotic led to be resistance against different drugs by animals in addition antibiotics transfer to ruminant product (milk or meat) which could threaten human health (Zhan et al, 2017;Bayat et al, 2018;Khattab, Abd El Tawab, Hadhoud, & Shaaban, 2020). So, European Union (EU) banned using antibiotics as feed additive, this radical change in laws resulted in an intensive development of research that relates to find effective natural compounds that could inhibit GHG and modulate the rumen fermentation (Matloup et al, 2017) Many studies have focused on the alternative strategies development to maintain animal productive performance and health (Khattab, Ebeid, Abd El Tawab, Abo El-Nor, & Aboamer, 2016;Khattab et al, 2017;Khattab & Tawab, 2018;Matloup et al, 2017).…”
Section: Introductionmentioning
confidence: 99%